2019
DOI: 10.1002/cphc.201801093
|View full text |Cite
|
Sign up to set email alerts
|

Direct Hydrogenation of Aluminum via Stabilization with Triethylenediamine: A Mechanochemical Approach to Synthesize the Triethylenediamine ⋅ AlH3 Adduct

Abstract: Two approaches for the synthesis of the triethylenediamine (TEDA) · AlH 3 adduct have been discovered. Both, the mechanochemical procedure and the wet chemical method lead to crystalline products. Starting from metallic Al powder and TEDA, ball milling under a pressure of 100 bar H 2 facilitates a direct hydrogenation of aluminum with conversions up to 90 %. Structure determination from X-ray powder diffraction data revealed an 1-D-coordination polymer of the type [TEDAÀ AlH 3 ] n .Furthermore, solid-state NMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…[13] Recently, the monomeric Al(I) compound Al(C 6 H-2,6-(C 6 H 2 -2,4,6-i Pr 3 ) 2 -3,5-i Pr 2 ) was described for hydrogen activation without the presence of a Lewis base. [14] Interestingly, it has been shown that aluminium metal can be mechanochemically hydrogenated in the presence of one equivalent of a triethylenediamine (TEDA) [15] or a transition metal catalyst and piperidine. [16] The CÀ H activation and hydroalumination of alkynes by the intramolecular AlÀ N compound (o-TMPÀ C 6 H 4 )AlH 2 ((2-(2,2,6,6tetramethyl-piperidin-1-yl)phenyl)-aluminium dihydride) have been previously reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Recently, the monomeric Al(I) compound Al(C 6 H-2,6-(C 6 H 2 -2,4,6-i Pr 3 ) 2 -3,5-i Pr 2 ) was described for hydrogen activation without the presence of a Lewis base. [14] Interestingly, it has been shown that aluminium metal can be mechanochemically hydrogenated in the presence of one equivalent of a triethylenediamine (TEDA) [15] or a transition metal catalyst and piperidine. [16] The CÀ H activation and hydroalumination of alkynes by the intramolecular AlÀ N compound (o-TMPÀ C 6 H 4 )AlH 2 ((2-(2,2,6,6tetramethyl-piperidin-1-yl)phenyl)-aluminium dihydride) have been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…Therein, the AlÀ N distance of 2.311(2) Å is significantly longer if compared to representative Al-N distances in similar compounds. Some selected representative compounds and their AlÀ N bond lengths are as follows, [Me 2 NÀ C 10 H 6 À AlH 2 ] 2 2.118(3) Å (hydride bridged dimer), [20] Me 3 NÀ AlMe 3 2.045(2) Å, [21] (Me 3 N) 2 AlH 3 2.163(2) Å, [22] [TEDAÀ AlH 3 ] n 2.161(2) Å (both AlÀ N distances are equal) [15] and TEDA-(AlMe 3 ) 2 2.065(8) Å. [23] FLPs and classic Lewis pairs can be discriminated by atomic distances.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, sublimation has also been used to remove volatile reactants used in excess in mechanochemical reactions, thus rendering pure nonvolatile product. For example, using this approach nonvolatile products such as the triethylenediamine (TEDA)⋅AlH 3 adduct, [23] and zeolitic imidazolate frameworks (ZIFs), [24] were easily isolated from their corresponding starting materials (Figure 3).…”
Section: Mechanochemistry and The Twelve Principles Of Green Chemistrymentioning
confidence: 99%
“…AlH 3 can react with a variety of organic compounds [119][120][121][122][123][124][125][126][127] . A variety of AlH 3 adducts of TMEDA (Me 2 NCH 2 CH 2 NMe 2 ), DIOX (O(CH 2 CH 2 ) 2 O), TEA (Et 3 N), BDMA (PhNMe 2 ), and TMPDA (Me 2 NCH 2 CH 2 CH 2 NMe 2 ) have been characterized by XRD, NMR, FT-Raman, FT-IR, DFT calculation, elemental analysis, and thermal analysis [126 , 127] .…”
Section: Regeneration Using Alh 3 Adductsmentioning
confidence: 99%